2020
DOI: 10.3390/plants9091179
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Trace Elements in the Water Fern Azolla filiculoides after Short-Term Application of Chestnut Wood Distillate (Pyroligneous Acid)

Abstract: Treatments of crops with additives to increase their productivity may pose environmental risks and induce negative effects also on non-target organisms. In this study, we investigated the potential effect of chestnut wood distillate (pyroligneous acid) used in agriculture, on the accumulation of trace elements in aquatic plants. As a model species, the common water fern Azolla filiculoides Lam. was selected, being often used also in phytoremediation processes. The content of selected elements of toxicological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…From a toxicological point of view, all treatments did not alter the content of the investigated elements in lettuce leaves, confirming the results obtained by Fačkovcová et al [15,16] about the environmental safety of WD. The concentrations of Fe, Zn, and Cu of our samples were within the common ranges reported in the literature: 1.97-8.6 mg/kg for Fe [45,46], 2.1-9.4 mg/kg for Zn [45][46][47], and 0.23-1.4 mg/kg for Cu [45,47].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…From a toxicological point of view, all treatments did not alter the content of the investigated elements in lettuce leaves, confirming the results obtained by Fačkovcová et al [15,16] about the environmental safety of WD. The concentrations of Fe, Zn, and Cu of our samples were within the common ranges reported in the literature: 1.97-8.6 mg/kg for Fe [45,46], 2.1-9.4 mg/kg for Zn [45][46][47], and 0.23-1.4 mg/kg for Cu [45,47].…”
Section: Discussionsupporting
confidence: 87%
“…There is convincing evidence that WD has great potential in agriculture [4,8,9] because of its ability to act as a biostimulant for crops, to increase biomass [10,11] and fruit production (quality, size, and weight) [6,12]. Moreover, ecotoxicological studies have confirmed that this product is safe for the environment since it has been shown to have no adverse effects on either aquatic or soil organisms [13,14], as well as non-target bioindicators, i.e., lichens, mosses, and aquatic ferns [15,16]. Additionally, an investigation of the safety profile of wood distillate excluded inflammatory and cytotoxic effects at low recommended doses and short-time applications at higher doses [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be emphasized that there is no correlation between natural and non-toxic as some natural compounds show a much greater toxicity than synthetic ones (i.e., botulin). Nevertheless, at routine usage doses, bio-based products have been shown to be safe, even for sensitive nontarget organisms [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence have been reported about the profitable use of WD extracted from different wood types, mainly owing to its antioxidant activity [12] and its derivates [13] on different soil organisms [14]. The ecotoxicology profile of WD was recently assessed on aquatic biota, excluding any risk of heavy metal accumulation in an aquatic fern model [15]. At the same time, some cytotoxic effects of natural extracts have been demonstrated, as in the case of essential oils commonly used in traditional Chinese medicine [16,17].…”
Section: Introductionmentioning
confidence: 99%